Transforming Civic Education Through Nationalism Projects to Strengthen Global Diversity Character in Higher Education - Nababan, Ramsul; Dharma, Surya; Siahaan, Parlaungan Gabriel; Junaidi; Fatimah, Ulfa; Faudzi, Wan Shazmien Daniel bin Mohamed (Jurnal Kewarganegaraan, 2025)
Globalization has influenced citizens' mindset, behavior, and attitudes, shifting traditional national values such as mutual cooperation, care, fairness, and mutual respect toward more individualistic and egocentric orientations. These changes pose a serious challenge to shaping national character, particularly among university students. This study aims to develop a Global Civics Learning Model Based on National Projects to strengthen students' character in embracing diversity. The research employed a Research and Development (R&D) approach using the 4-D model: Define, Design, Develop, and Disseminate. Data were analyzed using the Independent Sample T-Test to assess the model's effectiveness. The results indicate that the model has a very high level of validity, with content validation scoring an average of 94.72% and construct validation at 94.20%. Effectiveness testing revealed a significant difference between the experimental and control groups (sig. < 0.001), demonstrating the model’s effectiveness in enhancing students’ character related to global diversity. It is recommended that the model be applied more widely in civic education courses to cultivate national identity while promoting global citizenship values among students.